O percurso de constituição de duas professoras de anos iniciais sob a perspectiva da intelectualidade docente: desafios e possibilidades - Prado, Gilvonete Schimitz de (2016)
The purpose of this study is to look at the path of the making of professional practice under the bias of the teaching intelligentsia of two teachers from the state public network that would allow us to build an understanding of teaching as an intellectual function, as advocated by Giroux (1997; 1999) the theoretical framework we adopted. In this perspective, the analysis of paths was based on two distinct schools of investigation: a) With respect to forming elements suggesting a disqualification of the teacher's work and freeing her from critical and purposeful features, namely those from the models training and acting markedly homogenizing and linked to the educational policies and interests committed to standards of international organizations and the state’s political party programs. b) On the other hand, other current research explores the intellectual concept and claims it is possible to make this reference also to teachers. As to research methodology, we chose to develop in light of studies by Lahire (2004; 2005), about the construction of sociological portraits with regard to the interest of explicit trajectories of life and work to learn the provisions built from many socialization contexts that teachers, the subjects of this study, have been submitted to in life and because of that to meet the research objectives listed, which include: learning which provisions have been built and as configured by teachers in different socialization processes during their professional careers, so that the grasping of these provisions would allow us to affirm or not the power of a teaching intelligence taking them the design of a teacher as an intellectual as defended by Giroux. In the example of socializing experience, we highlight the participation of teachers in Practice Seminar organized by SEE-SP in 2013, while formative experience in this way, it was also our intention to examine to what extent the experience of the teachers surveyed at the seminar in question allowed them to apply to themselves and the work they have done on occasion, traits that they attributed themselves qualifying teachers as intellectuals. From the results of the survey, we highlight the following: engagement and commitment; clarity of their political and social function as well as their theoretical beliefs, recognizing their potential as scholars and active and reflective professionals. These provisions, built on the job of teaching, are presented as a work of these teachers differential which enabled visibility in them. Thus, participation in the Good Practice Seminar reinforced what they believed about education, expanding the look of the universe of activity in which they were inserted and giving them a greater awareness of themselves and the work they performed that could be exposed and employed with this experience.